The relative relationship between education and workplace task discretion: an international comparative perspective. Issue 1 (2nd January 2019) - Pullman, Ashley; Jongbloed, Janine
ABSTRACT: Through analyses of Programme for the International Assessment of Adult Competencies (PIAAC) data, the following study considers the direct and indirect association between education and workplace task discretion in 30 countries. By focusing on cross-national comparison, it considers the ways in which these findings are dependent on both the overall level and the range of task discretion across occupational sectors within a country. Theoretically, individual-agency and critical-institutional hypotheses are compared, two perspectives that provide divergent explanations for the indirect association between education and task discretion. The findings partially support both perspectives and there is strong evidence of a relative relationship between education and task discretion. That is, in country contexts where overall levels of task discretion are higher and more equal, education operates less strongly as a stratifying force. The originality of this approach showcases empirically how the association between education and task discretion is context dependent and theoretically how individual-agency and critical-institutional perspectives both contribute to understanding this relationship.